lntermodality and Intermodal Cargo Transport in the European Union - Rogić, Kristijan; Marinović, Pave; Luburić, Grgo (Promet - Traffic&Transportation, 2012)
Efficienttranspmt system is an essential prerequisite for thecompetitiveness of the European Union. The predicted increasein intemational trade, sudden expansion of the Union tothe middle and eastern European countries and widerco-peration of the Meditenmuan countries will make the roleof transportation even more significant.Unless the transpmt industry reconsiders its requirementfor modal-independent se1vices and uses the additional capacitiesin other modes of transpmt, the road traffic is likely to furtherincrease its share in the market, which amounts today to72%.In order to achieve social, economic and ecologicalsustainability, efficient and balanced use of the existing capacitiesin the overall traffic system of Europe has become the keychallenge.Therefore, the Community, among other things, strives towardsreal balance of the business policy which gives preferenceco the development of unique, integrated traffic systems for theCommunity as a whole.Promoting intermodality is a means of business policywhich enables systemic approach to traffic. Traffic services areoffered as modally independem links from home to home,based on a series of feasible alternatives regarding transportmode through a new, efficient implementation of the traffic systemthus reducing the transport costs and enabling creation ofadditional values.